Assisting Leadership Rehabilitation Program to support substitution and succession policy In the Jordanian Customs Department: Field Study - Jordan Customs Department - Al-Ta'ani, Einad Sayel (Journal of Economic, Administrative and Legal Sciences, 2020)
The main objective of this study is to answer the question of the role of leadership training programs in enhancing the leadership skills of the target customs officer in the leadership development programs، The researcher used the descriptive analytical method، The study community is staffed first class (University graduates and comprehensive diploma)، A random sample was selected () Employee From various departments.One of the main results of the study، according to the sample، is that the implementation of this program will enhance leadership skills، at the same time promoting confidence between staff and senior management in achieving fairness and transparency in selectionThe results of the study confirmed that there are no statistically significant differences in the role of the leadership training programs in enhancing the leadership skills of the employee if he participated in the programs of preparing leaders، The reasons are due to the type of job and training program. also there are statistically significant differences in the role of leadership training programs in the promotion of leadership skills from the point of view of the sample of the department's staff to the leadership development program.
Keywords: leadership preparation program; future leaders; Jordanian Customs Department; human resource development